pH-triggered clustering regulates β-sheet activation in silk assembly - Francis, Juanita; Houston, Judith; Jackson, Andrew; Dalgliesh, Robert; Martel, Anne; Porcar, Lionel; Roosen-Runge, Felix; Dicko, Cedric ; 0000-0001-6377-3500 (Communications Chemistry, 2026)
Silk fibres derive their exceptional properties from hierarchical protein organisation, yet the molecular pathways that guide this structural transformation remain poorly resolved. During regenerated silk fibroin gelation under biomimetic gradual acidification, we identify a stepwise assembly pathway comprising nanoscale clustering, domain growth within clusters, and mesoscale network formation. Time-resolved small-angle neutron scattering performed simultaneously with turbidity and fluorescence emission (NUrF) identifies unique intermediates and a regulated onset of β-contacts and β-sheets assembly, indicating that fibril formation requires prior compaction and network connectivity. By contrast, methanol-induced gelation bypasses these intermediates, driving rapid aggregation. These findings define the sequence and timing of events that construct silk’s hierarchical architecture without accidental aggregation, showing how pathway selection governs material outcomes. This multiscale resolution achieved by NUrF provides a broadly applicable strategy for probing hierarchical assembly in silk and other protein materials.